A glass menagerie of low complexity sequences. (June 2016) - Halfmann, Randal
Highlights: Proteins of low sequence complexity are predisposed to form metastable liquid phases. Liquid phases give way to amyloids or glasses. Glasses may be exceptionally proteotoxic. Glasses respond to time and stress, enabling proteins to store information. Abstract : Remarkably simple proteins play outsize roles in the execution of developmental complexity within biological systems. Sequence information determines structure and hence function, so how do low complexity sequences fulfill their functions? Recent discoveries are raising the curtain on a new dimension of the sequence-structure paradigm. In it, function derives not from the structures of individual proteins, but instead, from dynamic material properties of entire ensembles of the proteins acting in unison through phase changes. These phases include liquids, one-dimensional crystals, and — as elaborated herein — even glasses. The peculiar thermodynamics of glass-like protein assemblies, in particular, illuminate new principles of information flow through and, at times, orthogonal to the central dogma of molecular biology.